Affective Commitment among Faculties According to Academic Qualification and Faculty Group in Higher Education in Nepal - Kharel, Shreekrishna (KIC International Journal of Social Science and Management, 2022)
This article deals with the fundamental issues of affective commitment of faculties in higher education in Nepal. The main objective of this study is to investigate the relationship between faculty’s academic qualification and faculty group on affective commitment in faculty in higher education organizations. This follows a questionnaire survey of variables with a five-point Likert and uses mean, standard deviation, t/f test and Cronbach’s Alpha for analytical tools. The analyzed result shows a positive relationship between academic qualification and affective commitment. The analysis shows that higher qualification groups (PhD and M.Phil) are more emotionally attached than fewer qualification groups. The study shows no significant effect of faculty group on affective commitment. The sectoral sampling adequacy and a number of organizations represented in a survey may limit the general implication of results despite its analytical soundness. Moreover, may this study be originally picturesque and construes pre-cast for the future scenarios of the studied issues.